2018
DOI: 10.1007/s11892-018-0984-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Immune System in Diabetic Kidney Disease

Abstract: Diabetic kidney disease has not historically been considered an immune-mediated disease; however, increasing evidence is emerging in support of an immune role in its pathophysiology. Both systemic and local renal inflammation have been associated with DKD. Infiltration of immune cells, predominantly macrophages, into the kidney has been reported in a number of both experimental and clinical studies. In addition, increased levels of circulating pro-inflammatory cytokines have been linked to disease progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 112 publications
1
56
0
Order By: Relevance
“…The molecular mechanisms involved have also been elucidated, including oxidative stress [13,14], activation of nuclear factor kappa-B (NF-κB) [14], and production of related cytokines such as tumor necrosis factor (TNF) [13][14][15] and Toll-like receptor (TLR) activation [16]. Accordingly, targeting of macrophages has been extensively studied as an anti-inflammatory strategy [17]. In a recent review, we provided thorough information on the experimental and clinical studies reporting the beneficial effects of agents targeting inflammation pathways, such as monocyte protein-1 (MCP-1/CCL2), its receptor CCR2 (chemokine ligand 2/C-C-motif chemokine receptor type 2), IL-1β, and JAK/STAT (Janus kinase/signal transducer and activator of transcription), as well as Nrf2 (nuclear factor erythroid 2 related factor 2) inducers, e.g., bardoxolone methyl [18].…”
Section: Current Treatments Of Diabetic Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms involved have also been elucidated, including oxidative stress [13,14], activation of nuclear factor kappa-B (NF-κB) [14], and production of related cytokines such as tumor necrosis factor (TNF) [13][14][15] and Toll-like receptor (TLR) activation [16]. Accordingly, targeting of macrophages has been extensively studied as an anti-inflammatory strategy [17]. In a recent review, we provided thorough information on the experimental and clinical studies reporting the beneficial effects of agents targeting inflammation pathways, such as monocyte protein-1 (MCP-1/CCL2), its receptor CCR2 (chemokine ligand 2/C-C-motif chemokine receptor type 2), IL-1β, and JAK/STAT (Janus kinase/signal transducer and activator of transcription), as well as Nrf2 (nuclear factor erythroid 2 related factor 2) inducers, e.g., bardoxolone methyl [18].…”
Section: Current Treatments Of Diabetic Nephropathymentioning
confidence: 99%
“…Although these studies have addressed circulating or urinary IL-17A levels in DN patients, local renal levels of IL-17A have not been investigated yet. Importantly, infiltration of immune cells is a key feature of DN [17]. Activated T cells (CD4+ and CD8+) are mainly located in the renal interstitium of diabetic kidneys [44][45][46].…”
Section: Il-17 In Human Diabetic Nephropathymentioning
confidence: 99%
“…Among them we can mention peralin (pyraline) arising from the interaction of glucose with amino groups of proteins. In addition, the level of circulating proinflammatory cytokines contributing to the progression of kidney damage is increasing [47]. The accumulation of uric acid and glycated hemoglobin, as well as oxidative stress with increased activity of the renin-angiotensin-aldosterone system is important [48,49].…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…DN has not been traditionally considered an inflammatory disease until recently. Emerging data have demonstrated that tubulointerstitial inflammation is strongly correlated with the development and progression of DN (2,3). Macrophage infiltration in the kidney tissues has been postulated to be a prominent pathological feature and key inflammatory mediator during the progression of DN.…”
Section: Introductionmentioning
confidence: 99%